Eutectic mixture of Prilocaine and Lignocaine (2.5%) versus 5% Lignocaine versus placebo for pain relief in new-borns undergoing venipuncture: a hospital based, double blind randomised case control study - Reddy H. V., Rakshith; Rajan, Aswathy; Rao Aroor, Amitha (International Journal of Contemporary Pediatrics, 2019)
Background: Venipuncture is one of the most common cause of iatrogenic pain in neonates which is equally stressful to the parents as well as to the personnel performing the procedure. Despite an abundance of data that demonstrate the efficacy of local anesthetics for reducing venipuncture pain in neonates their use in day to day practice is not used widely used. Our objective was to evaluate the efficacy of EMLA cream and 5% Lignocaine cream versus placebo for pain relief in newborns undergoing venipuncture. Methods: Present study was a hospital based, double blind randomised, case control study. A 240 eligible new-borns were randomised into EMLA, 5%lignocaine and placebo groups after randomization. The respective creams were applied 1 hour before the procedure and pain scores were assessed using NIPS scoring during venepunture. Data was analysed using SPSS ver. 20.0 statistical package. Student’s unpaired t-test and paired t tests was used to compare continuous data, and to compare pain scores one-way ANOVA was used to compare categorical data. A p-value <0.05 was considered statistically significant. Results: Paired t-tests revealed significant lower NIPS scores in EMLA and 5% lignocaine group than the placebo group (p value=0.001). Conclusions: From present study it can be concluded that both EMLA and 5% lignocaine are equally efficacious and cost effective in reducing the pain of venepuncture in neonates.